Synthesis, Structure, and Electrophysical and Electrochemical Properties of Novel Composite La0.9MnO3-LaFeO3 - Mukhametkali Mataev; Zamira Sarsenbaeva; Bahadir Keskin; Marzhan Nurbekova; Amangeldi Meldeshov; Zhanar Tursyn; Karima Seitbekova (Molecules)
This article presents the synthesis, electrophysical, and catalytic properties of a La0.9MnO3–LaFeO3 nanocomposite material. The nanocomposite was synthesized via the sol–gel (Pechini) method. X-ray diffraction (XRD) analysis revealed a polycrystalline, biphasic perovskite structure combining both hexagonal and cubic symmetry. The microstructure and elemental composition, examined using field emission scanning electron microscopy (FESEM), indicated an average particle size of approximately 186.9 nm. The composite exhibits semiconducting behavior within the temperature ranges of 293–323 K and 343–393 K. Developing electrocatalysts free of precious metals for the hydrogen evolution reaction (HER) is increasingly important to facilitate the production of hydrogen from renewable sources. In this study, the conductive La0.9MnO3–LaFeO3 composite was deposited on graphite and, for the first time, evaluated as an electrocatalyst for HER in acidic media. The resulting composite films were tested using linear sweep voltammetry (LSV) and electrochemical impedance spectroscopy (EIS) in a glassy carbon electrode (GCE) setup, providing insights into their potential as effective, cost-efficient electrocatalysts.